2013
DOI: 10.2519/jospt.2013.4221
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Combined Effects of Thoracic Spine Thrust Manipulation and Cervical Spine Nonthrust Manipulation in Individuals With Mechanical Neck Pain: A Randomized Clinical Trial

Abstract: Study Design Randomized clinical trial. Objective To investigate the short-term effects of thoracic spine thrust manipulation combined with cervical spine nonthrust manipulation (experimental group) versus cervical spine nonthrust manipulation alone (comparison group) in individuals with mechanical neck pain. Background Research has demonstrated improved outcomes with both nonthrust manipulation directed at the cervical spine and thrust manipulation directed at the thoracic spine in patients with neck pain. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 55 publications
3
80
1
2
Order By: Relevance
“…The results of this study demonstrated that patients who had mechanical neck pain benefited from thoracic spine HVLA thrust along with the conventional treatment which included isometric exercises, range of motion exercises and stretching exercises of the trapezius and levator scapulae muscles. The results of this study are consistent with the previous studies done so far that have demonstrated the effectiveness of thoracic spinal manipulation along with cervical spine thrust and non thrust manipulation plus exercises in patients with mechanical neck pain [3]. The significance of this study is that along with its long term benefits as proved in previous researches, HVLA thrust of the thoracic spine has an immediate beneficial effect on pain in patients with mechanical neck pain.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The results of this study demonstrated that patients who had mechanical neck pain benefited from thoracic spine HVLA thrust along with the conventional treatment which included isometric exercises, range of motion exercises and stretching exercises of the trapezius and levator scapulae muscles. The results of this study are consistent with the previous studies done so far that have demonstrated the effectiveness of thoracic spinal manipulation along with cervical spine thrust and non thrust manipulation plus exercises in patients with mechanical neck pain [3]. The significance of this study is that along with its long term benefits as proved in previous researches, HVLA thrust of the thoracic spine has an immediate beneficial effect on pain in patients with mechanical neck pain.…”
Section: Discussionsupporting
confidence: 82%
“…Alterations in one part of the spine can cause compensatory or beneficial changes in the other parts of the spine. Due to manipulation of the thoracic spine, the biomechanical relationship between the thoracic spine and cervical spine improves thus causing reduction of mechanical stress on the pain generators [3]. Muscles adjacent to and opposite to the site of manipulation elicit a response due to manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations